2021
DOI: 10.4103/jfmpc.jfmpc_1456_20
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smoking cessation counseling favorable practice for primary care physicians

Abstract: Background: Smoking cessation counseling is not well established in Middle East countries including Palestine. This study assesses the practice of smoking cessation counseling among primary healthcare (PHC) physicians in Palestine and its determinants. Methods: Over the period from April to September 2019, general practitioners, family medicine physicians, obstetricians and gynecologists, and dentists working at the PHC Centers in Palestine were approached through a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In our study, it is seen that the frequency of physicians receiving smoking cessation counseling training fell far behind this target. In studies conducted in Türkiye and Palestine, it was reported that very few primary care physicians received smoking cessation counseling training [ 9 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, it is seen that the frequency of physicians receiving smoking cessation counseling training fell far behind this target. In studies conducted in Türkiye and Palestine, it was reported that very few primary care physicians received smoking cessation counseling training [ 9 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that providing smoking cessation counseling training to primary care physicians increases both the frequency and effectiveness of smoking cessation interventions [ 29 ]. In addition, it has been shown in many cross-sectional studies in the literature that physicians who have received training in smoking cessation counseling provide smoking cessation counseling more frequently [ 7 , 9 , 18 , 20 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%